ANALISIS EFEKTIVITAS TRANSMISI MONETER GANDA TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Muhammad Ghafur Wibow; Ahmad Mubarok (Jurnal Ekonomi dan Pembangunan, 2025)
The mechanism of monetary policy that affects economic growth is called as monetary policy transmission mechanism. Indonesia embraces a dual banking system, i.e. sharia and conventional bank. Bank Indonesia as the monetary authority has sharia transmission mechanism instruments and conventional transmission mechanism instruments. The purpose of this research is to analyze the double monetary transmission effectiveness applying sharia schemes, namely financing and profit sharing, and conventional schemes: credit and interest rate scheme, in order to boost economic growth. This research applies the data in the period of 2008-2015. Data calibration process employs stationery test, co-integration test, stability test, causality test, impulse response function analysis, and forecast error variance decomposition. The result finds that the variable of sharia pathway is effective financing to promote economic growth. Variable of profit sharing and SBIS are not effective to promote economic growth. The variables of conventional schemes which are of total on credit and SBI are not effective in boosting economic growth while interest rate credit is effective to promote it.